The comparative investigation of the lipophilic compounds of Portulaca oleracea L. and Portulaca grandiflora Hook - Kinichenko, A. O.; Кініченко, Анна Олександрівна (My University, 2018)
Aim. The comparative investigation of the lipophilic compounds of Portulaca oleracea L. and Portulaca grandiflora Hook.
Keywords: тези доповідей